Pengaruh Komponen Influencer Marketing terhadap Minat Beli Buah Durian di House of Durian Bali - SUTEJA, I DEWA GEDE ARI PRATYAKSA; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
The Impact of Influencer Marketing Components on the Purchasing Intention of Durian Fruit at House of Durian Bali.  The significant impact wielded by influencer has given rise to a new marketing approach known as influencer marketing. House of Durian Bali is a company that collaborates with influencer as part of its marketing strategy to expand its market reach. The research aims to identify the implementation of influencer marketing and analyze the impact of influencer marketing components on the purchasing interest of durian fruits at House of Durian Bali. The research sample was obtained using the purposive sampling technique, involving a total of 96 respondents. Data was collected through surveys, interviews, and questionnaires. The analysis used is a qualitative descriptive method and the SEM-PLS with SmartPLS 4 software. The findings reveal that House of Durian Bali utilizes influencer marketing to target its market effectively. Collaboration with mega and macro influencer occurs through sponsored content, involves implementation stages from influencer identification to content evaluation. The influencer marketing components such as trustworthiness, expertise, attractiveness, and respect positively and significantly influence the purchasing interest in durian fruits at House of Durian Bali. The company is encouraged to continue implementing influencer marketing and explore additional collaboration types, such as giveaways or influencer takeovers, for further development.